2021
DOI: 10.1021/acsomega.0c03980
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Influence of the Crystallographic Orientation of Cassiterite Observed with Colloidal Probe Atomic Force Microscopy and its Implications for Hydrophobization by an Anionic Flotation Collector

Abstract: In this study, the physicochemical behaviors of the ( 110), (100), as well as (001) of SnO 2 were investigated by using high-resolution direct force spectroscopy. The measurements were conducted between a silica sphere and sample surfaces in 10 mmol/L KCl between pH 3.1 and 6.2 using colloidal probe atomic force microscopy (cp-AFM-hydrophilic). Dissimilar interactions were detected on different-oriented surfaces. The pH values where the force switched from positive to negative can be clearly distinguished and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Zhu et al analyzed the reactivity of different crystal planes of spodumene with the help of the D b method. Similar application of the D b method is also reflected in the adsorption behaviors of the anionic collector on the different surfaces of cassiterite studied by Wu et al…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…Zhu et al analyzed the reactivity of different crystal planes of spodumene with the help of the D b method. Similar application of the D b method is also reflected in the adsorption behaviors of the anionic collector on the different surfaces of cassiterite studied by Wu et al…”
Section: Introductionmentioning
confidence: 67%
“…Song et al 16 found that the (112) surface with a smaller broken bond density is more likely to be broken than the (001) surface, thereby explaining the cleavage characteristics and exposed surface properties of wulfenite. Wang et al 17 application of the D b method is also reflected in the adsorption behaviors of the anionic collector on the different surfaces of cassiterite studied by Wu et al 19 Surface energy is another method commonly used to characterize surface reactivity and the surface fracture possibility. 20 It is generally believed that the lower the surface energy, the higher the stability of the crystal face and the greater the fracture probability.…”
Section: Introductionmentioning
confidence: 99%
“…In our calculations, we choose the most stablest SnO 2 (110) surface as the research surface [60,61], which is modeled by a periodic 3 × 1 plate with 3 layers. To avoid the interaction of adjacent adsorbates, a vacuum layer of 15 Å was added to the SnO 2 model.…”
Section: Computational Detailsmentioning
confidence: 99%